Objectively measured physical activity and symptoms of psychopathology in general population adolescents from the SIGMA cohort. (October 2021) - Hagemann, Noëmi; Kirtley, Olivia J.; Lafit, Ginette; Wampers, Martien; Achterhof, Robin; Hermans, Karlijn S.F.M.; Hiekkaranta, Anu P.; Lecei, Aleksandra; Vancampfort, Davy; Myin-Germeys, Inez
Abstract: Background: Less physical activity (PA) has been associated with the development of psychopathology in adolescence. Few studies, however, have focused on understanding the nature of the PA – psychopathology relationship and existing research relies mostly on self-report PA measures, which are less reliable. In this study, we investigated the nature of the relationships between objectively measured light physical activity (LPA) and moderate-vigorous physical activity (MVPA), and psychopathology symptoms in adolescents. Methods: 934 adolescents (63% female) aged 11–19 years from the SIGMA cohort wore the Fitbit Charge 2 measuring LPA and MVPA during at least three days. Participants completed the Brief Symptom Inventory-53, assessing general symptoms of psychopathology, depression, anxiety, and psychoticism. Model selection was conducted in a subset of the dataset (n = 464) to determine the best fit. The optimal model was then fitted to the remainder of the dataset (n = 470). Results: The results from the selected linear model indicated a non-significant relationship between LPA, MVPA, and symptoms of general psychopathology, depression, anxiety, and psychoticism. Conclusions: This study does not provide evidence that higher durations of LPA and MVPA alone relate to reduced symptoms of general psychopathology, depression, anxiety, and psychoticism in the general adolescent population. A more integrative approach considering the interdependency of multiple lifestyle factors, as well as the domain, context, and individual experience of PA may add value to the understanding of the PA-psychopathology relationship. Highlights: We explored the nature and associations of the physical activity -psychopathology relationship. Objectively measured physical activity was not associated with symptoms of psychopathology. Considering domain and context of physical activity may add value to understanding the relationship.